Conflicts Faced by Main Characters in “Red, White & Royal Blue” Movie (Jurnal Pustaka, 2026)
One of the most essential elements in developing a story is the existence of conflict, a story without conflict certainly does not be able to create a storyline. This study entitled “Conflicts Faced by Main Characters in Red, White & Royal Blue Movie”. The aims of this study is to investigate the types of conflict faced by main characters in “Red, White & Royal Blue” movie. The data in this study was taken from a romance movie entitled “Red, White & Royal Blue” directed by Matthew Lopez. The method used in collecting data was documentation method with note taking technique. In analyzing data, this study used descriptive qualitative method. Then, informal method is used in presenting the data. Theory used to support this study is types of conflict theory proposed by Kenney (1966) which used to find out what types of conflict faced by the main character in the “Red, White & Royal Blue” movie. The results of the study showed that main characters, Alex Claremont-Diaz and Prince Henry faced two types of conflict, namely internal conflicts and external conflicts in the “Red, White & Royal Blue” movie. The external conflicts faced by the main characters occurred between man against man and man against society. Meanwhile, the internal conflict occurred between the main characters and themselves
Keywords: Conflict; Main Character; Movie